2002
DOI: 10.1006/dbio.2002.0605
|View full text |Cite
|
Sign up to set email alerts
|

The IGF Pathway Regulates Head Formation by Inhibiting Wnt Signaling in Xenopus

Abstract: The insulin-like growth factors (IGFs) are well known mitogens, both in vivo and in vitro, while functions in cellular differentiation have also been indicated. Here, we demonstrate a new role for the IGF pathway in regulating head formation in Xenopus embryos. Both IGF-1 and IGF-2, along with their receptor IGF-1R, are expressed early during embryogenesis, and the IGF-1R is present particularly in anterior and dorsal structures. Overexpression of IGF-1 leads to anterior expansion of head neural tissue as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 52 publications
5
86
0
Order By: Relevance
“…13,14 Several studies in Xenopus, however, suggested that IGF1R signaling induces the formation of anterior neural tissue, the cellular basis for which was change in cell fate. 15,16 A similar study in zebrafish was also reported. 17 Thus, there is a major discrepancy concerning the cellular basis for the conserved IGF1R signaling cascade during vertebrate development.…”
supporting
confidence: 62%
See 3 more Smart Citations
“…13,14 Several studies in Xenopus, however, suggested that IGF1R signaling induces the formation of anterior neural tissue, the cellular basis for which was change in cell fate. 15,16 A similar study in zebrafish was also reported. 17 Thus, there is a major discrepancy concerning the cellular basis for the conserved IGF1R signaling cascade during vertebrate development.…”
supporting
confidence: 62%
“…These phenotypes are consistent with those reported in mutant mice 11,12,23 and Drosophila 24 but differ from previous studies in Xenopus. 15,16 Although IGF signaling was proposed to be an anteriorizing or neural induction signal in Xenopus, 15,16 our results show that reduction of Igf signaling not only affects retina, but also other tissues throughout the zebrafish embryo. This is most evident in disrupted CaP motoneuron survival and increased apoptosis in the spinal cord.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…It is reasonable that an EYA3-specific cofactor or a specific mix of cofactors exists in the anterior neuroectoderm, because we found that the hyperplasia of the brain upon Xeya3 overexpression was strictly limited to this area. In Xenopus, hyperplasia of the forebrain region was also observed upon the activation of the insulin-like growth factor or upon repression of canonical Wnt signalling pathways, respectively, and by overexpression of either Six3 or Six6 (Zuber et al, 1999;Bernier et al, 2000;Pera et al, 2001;Richard-Parpaillon et al, 2002;Lagutin et al, 2003). However, in all these cases, the increase of forebrain tissue was explained by a transdifferentiation/determination of non-neural tissue, which was not observed upon Xeya3 overexpression.…”
Section: Potential Protein Interaction Partners Of Eya3mentioning
confidence: 98%